The Transformation of Wordwall as an Educational Tool: A Reconstruction of Effective Qurdis Learning - Nabilah Hayyu Palupi; Rifa Muslihatin Nufus (Al-Qalam Institue, 2026)
This study aims to analyze the transformation of Wordwall learning media in Qurdis instruction and its impact on student engagement, motivation, and participation in learning. This research employed a qualitative case study design. Data were collected through observation, in-depth interviews, and documentation involving teachers, students, and school administrators. Data analysis was conducted using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that the use of Wordwall transforms Qurdis learning into a more interactive, participatory, and enjoyable process. Students become more active in classroom activities, demonstrate higher motivation to learn, and show better understanding of the learning materials. Furthermore, the learning interaction shifts from a teacher-centered approach to a student-centered approach, encouraging greater student involvement in the learning process. The study implies that digital learning media can serve as an effective educational innovation to enhance the quality of Islamic education and support learning practices that are more responsive to technological developments and the needs of digital-age learners.